The benthic fauna of Western African Lagoon (the lake Nokoué in Bénin) - (:unkn) unknown (My University, 2006)
Invertebrates are a key component of aquatic ecosystems even if they are quite often unknwon or poorly documented. This study concerns the invertebrate fauna of a West African lagoon, their contribution to the food web, and their possible use in order to assess the the ecological condition of the lake. A sampling of all the invertebrates was carried out during two years and the pattern of spatial and seasonal distribution was obtained in terms of density and biomass. Pollutions and, to a lesser extent, salinity, play a key role in the distribution of this fauna. Therefore, a biological indice could be designed for a quick evaluation and monitoring of the health of any West African brackish water. Finally, the contribution of the invertebrates to the foodweb was evaluated on a quantitative basis. Resulting proposals for sustainable management and exploitation of the living resourcs of the lake were elaborated and discussed.
Keywords: African Research